MELACAK PEMIKIRAN PEMBARUAN HUKUM ISLAM DI INDONESIA - Rahman, Budiarti A. (DIKTUM: Jurnal Syariah dan Hukum, 2014)
Efforts to reform Islamic law, among others, characterized by attempts a review of materials jurisprudence based on the reinterpretation of the texts. This is done because the interpretation of the results given earlier scholars are very thick with the conditions of his time which is certainly different from the situation today. So, the update is needed for the actualization of Islamic teachings relating to the rule of law as contained in the texts. In this case, does not mean changing or leaving the texts of the Qur'an or hadith of the Prophet, but just update the interpretation of the texts to fit with the times. This study is intended to explore some of the basics of thought leaders who are giving birth to a step-by-step reform of Islamic law in Indonesia. Through the identification and exploration of the reformers thought leaders can be affirmed that in some aspects of Islamic law is needed contextualization or development taking into account the social conditions and the times in order to continue dialectic with people's lives and the growing age.